PERAN KOLESTEROL HDL TERHADAP PENYAKIT KARDIOVASKULER DAN DIABETES MELLITUS - Tuminah, Sulistyowati (GIZI INDONESIA, 2009)
ROLE OF HDL-CHOLESTEROL ON CARDIOVASCULAR DISEASE AND DIABETES MELLITUSMortality in Indonesia which caused by cardiovascular disease showed an enhancing prevalent. Oneof the risk factors of cardiovascular disease is Dyslipidemia, marked by increasing on total,triglycerides and LDL but decreasing on HDL cholesterol. HDL cholesterol is a good cholesterol thathas an important role in prevention of cardiovascular disease as well as diabetes mellitus. Two kindsof natural matters have known as elevator for HDL cholesterol are dark chocolate and virgin coconutoil.Keywords: cardiovascular disease, HDL cholesterol, diabetes mellitus